Alaska summary report - Outer Continental Shelf Oil and Gas Information Program (U.S.); United States. Minerals Management Service
Description based on: June 1984-Dec. 1985. Mode of access: Internet. Merged with: Alaska index, to form: Alaska summary/index. Formed by the union of: Arctic summary report, Bering Sea summary report, and: Gulf of Alaska summary report.